Current status, uncertainty and future needs in soil organic carbon monitoring - Jandl, Robert; Rodeghiero, Mirco; Martinez, Cristina; Cotrufo, M. Francesca; Bampa, Francesca; van Wesemael, Bas; Harrison, Robert B; Guerrini, Iraê Amaral [UNESP]; Richter, Daniel deB; Rustad, Lindsey; Lorenz, Klaus; Chabbi, Abad; et al. (Elsevier, 2014)
Increasing human demands on soil-derived ecosystem services requires reliable data on global soil resources for sustainable development. The soil organic carbon (SOC) pool is a key indicator of soil quality as it affects essential biological, chemical and physical soil functions such as nutrient cycling, pesticide and water retention, and soil structure maintenance. However, information on the SOC pool, and its temporal and spatial dynamics is unbalanced. Even in well-studied regions with a pronounced interest in environmental issues information on soil carbon (C) is inconsistent. Several activities for the compilation of global soil C data are under way. However, different approaches for soil sampling and chemical analyses make even regional comparisons highly uncertain. Often, the procedures used so far have not allowed the reliable estimation of the total SOC pool, partly because the available knowledge is focused on not clearly defined upper soil horizons and the contribution of subsoil to SOC stocks has been less considered. Even more difficult is quantifying SOC pool changes over time. SOC consists of variable amounts of labile and recalcitrant molecules of plant, and microbial and animal origin that are often operationally defined. A comprehensively active soil expert community needs to agree on protocols of soil surveying and lab procedures towards reliable SOC pool estimates. Already established long-term ecological research sites, where SOC changes are quantified and the underlying mechanisms are investigated, are potentially the backbones for regional, national, and international SOC monitoring programs. © 2013 Elsevier B.V.
Keywords: Long-term ecological research; Long-term soil experiment; Soil carbon change; Soil monitoring; Soil organic carbon pool